The Quality Of Organizational Communication And Its Role In Achieving The Effectiveness Of Electronic Management (Revue El-Wahat pour les Recherches et les Etudes, 2025)
Electronic administration has become a wide world for interaction and communication across borders between institutions, and by adapting to the new trend of openness, the technology represented by communication networks makes the Internet and the things accompanying it a fertile and spacious ground for use and interaction with the rules and transactions of electronic administration، this study provides a theoretical framework for the concept of electronic management and the concept of organizational communication by focusing on the quality of organizational communication in achieving the performance of business institutions in this new field in various administrative matters. Applications of electronic management have identified the necessity of adopting quality organizational communication for the application of electronic management.Keywords:organizational communication, electronic management, business institutions.